Photocatalytic Degradation of Naphthol Blue Black Using TiO2-Chitosan Catalyst Under Solar Energy - Utami Irawati; Taufiqur Rohman; Khairun Nisa (Jurnal Ilmiah Berkala Sains dan Terapan Kimia, 2024)
Naphthol blue black (NBB) is an aromatic azo compound that is potentially carcinogenic and mutagenic. An alternative method of dealing with dye waste is photocatalysis. Photocatalysis is a combination of photochemical processes with the use of catalysts. The purpose of this study is to obtain data on the ratio of TiO2: Chitosan, which produces composites with the best ability, irradiation time and optimum dose of TiO2, which is effective in the process of photodegradation of NBB. The process of NBB photodegradation by chitosan beads and composites and chitosan irradiated with the best irradiation time on reducing NBB levels is for 360 minutes with a decrease in concentration of NBB more than 80%. Beads composite TiO2: Chitosan ratio of 5: 10 produces optimal ability. The optimum dose of composite beads in the NBB photodegradation process is 1 g composite / 100 mL solution.